Foreign Experience in Developing the Digitalization Activities of O‘zbekiston Pochtasi JSC - Mamatqulov , G‘ulom (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This study analyzes the digital transformation of O‘zbekiston Pochtasi JSC within the framework of global postal modernization processes. The transition from traditional postal services to integrated digital logistics platforms, the development of unified information systems, e-commerce integration, smart delivery systems, and mobile applications are highlighted. The research results demonstrate that automation, real-time tracking, and centralized data management improve service quality and operational efficiency. Digitalization enhances economic efficiency, expands accessibility to services, and strengthens the role of the postal system in the digital economy.